MODEL PENGEMBANGAN MANAJEMEN RESIKO TERHADAP PROSES PERKEMBANGAN KEILMUAN - Putri Syahri (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Risk management as an effort in managing every step, target and scope of the process in the field of science that needs to be understood in more detail so that its implementation can run according to expectations. Because basically there is no risk that can be eliminated at all. The steps that can be taken are to overcome the risk in a more accountable way. Reducing risk by implementing appropriate systems and procedures for organizations or institutions appropriately can be a way to minimize the impact of risks that occur later. In implementing the development of risk management, the impact on current scientific developments is an effort from various parties to strengthen the position of risk management in overcoming errors, especially in scientific developments in the future. This certainly goes hand in hand with what has been a concern in risk control that has been measured and calculated in such a way.